PENGARUH MODEL PEMBELAJARAN INQUIRY BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR IPAS MATERI BAGIAN TUBUH TUMBUHAN PADA MURID KELAS IV SD NEGERI 1 BEBALANG BANGLI - Rini, Ni Komang; Sutriyanti, Ni Komang; Mahendradhani, Gusti Ayu Agung Riesa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science and Social Studies (IPAS) learning in elementary schools plays an important role in building students’ understanding of scientific concepts. However, in practice, IPAS learning tends to be teacher-centered and does not sufficiently involve students actively, which results in low learning outcomes, especially on the topic of plant body parts. This study aims to determine the effect of the Inquiry Based Learning (IBL) model assisted by interactive learning media on IPAS learning outcomes in the topic of plant body parts among fourth-grade students at SD Negeri 1 Bebalang Bangli. This research used a quantitative approach with an experimental method and a Pre-Experimental Design in the form of a One Group Pretest–Posttest Design. The subjects of the study were 25 fourth-grade students. Data collection techniques used learning achievement tests in the form of pretest and posttest. The data were analyzed using the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain Score test. The results showed that the average pretest score of 68,84 increased to 82,24 in the posttest, with an increase of 13,40 points. Learning mastery also increased from 8 students (32%) in the pretest to 25 students (100%) in the posttest. The Paired Sample t-Test results showed a significance value of < 0.001 < 0.05, indicating a significant effect. In addition, the N-Gain Score result of 0.4155 was in the medium category. Based on these findings, it can be concluded that the implementation of the Inquiry Based Learning model assisted by interactive learning media has a significant effect on IPAS learning outcomes of fourth-grade students at SD Negeri 1 Bebalang Bangli.